2017
DOI: 10.1038/s41598-017-06455-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory potential of diet and risk of cardiovascular disease or mortality: A meta-analysis

Abstract: Inconsistent findings have reported on the inflammatory potential of diet and cardiovascular disease (CVD) and mortality risk. The aim of this meta-analysis was to investigate the association between the inflammatory potential of diet as estimated by the dietary inflammatory index (DII) score and CVD or mortality risk in the general population. A comprehensive literature search was conducted in PubMed and Embase databases through February 2017. All prospective observational studies assessing the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 35 publications
5
30
1
4
Order By: Relevance
“…Our results are in line with findings based on the DII (opposite scoring direction to the AIDI) . In a meta‐analysis of prospective studies, associations between the DII and all‐cause (for higher versus lower pro‐inflammatory diet potential: HR: 1.22, 95% CI: 1.06–1.41), CVD (HR: 1.28, 95% CI: 1.04–1.58) and cancer mortality (HR: 1.24, 95% CI: 1.01–1.51) were observed . One of the studies included in the meta‐analysis was conducted in the same population of women as in the present study (the SMC), and a significant association between the DII and all‐cause mortality (the highest versus the lowest quintile of the DII: HR: 1.25, 95% CI: 1.07–1.47, P for trend = 0.003) was observed, whilst nonsignificant trends towards associations with CVD (HR: 1.26, 95% CI: 0.93–1.70, P for trend = 0.08) and cancer (HR 1.25, 95% CI: 0.96–1.64, P for trend = 0.14) mortality were demonstrated .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are in line with findings based on the DII (opposite scoring direction to the AIDI) . In a meta‐analysis of prospective studies, associations between the DII and all‐cause (for higher versus lower pro‐inflammatory diet potential: HR: 1.22, 95% CI: 1.06–1.41), CVD (HR: 1.28, 95% CI: 1.04–1.58) and cancer mortality (HR: 1.24, 95% CI: 1.01–1.51) were observed . One of the studies included in the meta‐analysis was conducted in the same population of women as in the present study (the SMC), and a significant association between the DII and all‐cause mortality (the highest versus the lowest quintile of the DII: HR: 1.25, 95% CI: 1.07–1.47, P for trend = 0.003) was observed, whilst nonsignificant trends towards associations with CVD (HR: 1.26, 95% CI: 0.93–1.70, P for trend = 0.08) and cancer (HR 1.25, 95% CI: 0.96–1.64, P for trend = 0.14) mortality were demonstrated .…”
Section: Discussionsupporting
confidence: 90%
“…The index used in the present study has been validated against high‐sensitivity C‐reactive protein (hsCRP) and was independent of age, smoking status, trunk fat mass, nonsteroidal anti‐inflammatory drug use, hormone‐replacement therapy use and chronic diseases, and could be used even amongst individuals with hsCRP <3 mg L −1 . Our results are in line with findings based on the DII (opposite scoring direction to the AIDI) . In a meta‐analysis of prospective studies, associations between the DII and all‐cause (for higher versus lower pro‐inflammatory diet potential: HR: 1.22, 95% CI: 1.06–1.41), CVD (HR: 1.28, 95% CI: 1.04–1.58) and cancer mortality (HR: 1.24, 95% CI: 1.01–1.51) were observed .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Proponents of Mediterranean-type and DASH-type (Dietary Approaches to Stop Hypertension) diets suggest that these diets can improve risk factors for cardiovascular disease through weight loss itself and owing to their limited sodium content and claimed anti-inflammatory properties 9. Systematic reviews and meta-analyses have shown conflicting results for the dietary effect on markers of cardiovascular disease risk, including blood pressure, low density lipoprotein (LDL) and high density lipoprotein (HDL) cholesterol, and C reactive protein 689101112. Few reviews have used rigorous meta-analytical techniques to obtain quantitative estimates of the relative effect of different diets 41314.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent meta-analyses concluded that pro-inflammatory diets are independently associated with an increased risk of all-cause and cardiovascular mortality, and CVD in the general population. This association highlights the fact that a low inflammatory diet could reduce CVD risk (Shivappa et al, 2018;Zhong et al, 2017). However, even though data from a representative national sample of 2,889 Spanish children and young people revealed that diet quality was linked to greater anti-inflammatory potential (Bawaked et al, 2017), there are no data on the potential role of an inflammatory diet in regard to cardiovascular risk factors in populations of young people.…”
mentioning
confidence: 97%